Edukasi Manfaat Vaksinasi Mengenai Dampak Infeksi Covid-19 di SMKS 9 Muhammadiyah Kota Bengkulu - Dita, Diah Ayu Aguspa; Ocktaviani, Risti Dwi; Sariyanti, Mardhatillah; Rizqoh, Debie (Universitas Bengkulu, 2022)
The COVID-19 pandemic is a major challenge to Indonesia’s to improve public health. Vaccination has been increased in the fight against COVID-19. The education goal is to raise awareness about the advantages of COVID-19 vaccination. Ten teachers and education staff are taking part in this community service project. This activity began with completing a pre-test questionnaire about the advantages of the COVID-19 vaccination, followed by counseling from expertise and completing the post-test questionnaire. The results of the questionnaire evaluation after counseling improved by 95%, indicating a better understanding of the advantages of COVID-19 vaccination. Throughout the outreach activities, all participants were enthusiastic about the material presented while also discussing the hoaxes that were currently circulating in the community.